Structural characterization of a UbiA superfamily member of archaeal origin - Boral, Debjyoti; Ramasamy, Suresh Kumar (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Lipid biosynthesis; UbiA superfamily

Baicalein suppresses repeat tau fibrillization by sequestering oligomers - Sonawane, Shweta Kishor; Balmik, Abhishek Ankur; Boral, Debjyoti; Ramasamy, Sureshkumar; Chinnathambi, Subashchandrabose (Archives of Biochemistry and Biophysics, 2019)
Alzheimer's disease (AD) is a neurodegenerative disorder caused by protein misfolding, aggregation and accumulation in the brain. A large number of molecules are being screened against these pathogenic proteins but the focus for therapeutics is shifting towards the natural compounds as aggregation inhibitors, mainly due to their minimum adverse effects. Baicalein is a natural compound belonging to the class of flavonoids isolated from the Chinese herb Scutellaria baicalensis. Here we applied fluorescence, absorbance, microscopy, MALDI-TOF spectrophotometry and other biochemical techniques to investigate the interaction between Tau and Baicalein in vitro. We found the aggregation inhibitory properties of Baicalein for the repeat Tau. Overall, the potential of Baicalein in dissolving the preformed Tau oligomers as well as mature fibrils can be of utmost importance in therapeutics for Alzheimer's disease.
Keywords: Alzheimer disease; Baicalein; Microtubule assembly; Paired helical filaments; Protein aggregation; tau protein

Structural insight into a membrane intrinsic Acyltransferase from Chlorobium tepidum - Boral, Debjyoti; Vankudoth, Koteswara Rao; Ramasamy, Sureshkumar (Current Microbiology, 2019)
The Lipid A component of the outer membrane of Gram-negative bacteria is an integral part of the permeability barrier known as LPS, which actively prevents the uptake of bactericidal compounds. It is clinically very significant, as it is known to elicit a strong immune response in the humans, through the TLR4 complex. The Lipid A species are synthesized through a highly conserved multistep biosynthetic pathway. The final step is catalyzed by acyltransferases of the HtrB/MsbB family, which are members of a superfamily of enzymes, present in all domains of life with important roles to play in various biological processes. The investigation of a putative dual functioning enzyme which can add both laurate and myristate residues to the (Kdo)(2)-lipid IVA (precursor of Lipid A) would give a snapshot into the versatility of substrates that these enzymes catalyze. In this study we have cloned and purified to homogeneity, such a putative dual functional acyltransferase from Chlorobium tepidum, and attempted to study the enzyme in more details in terms of its sequence and structural aspects, as it lacks conserved residues with other enzymes of the same family.

Archeal Di-O-geranylgeranyl glyceryl phosphate synthase of a UbiA superfamily member provides insight into the multiple human diseases - Boral, Debjyoti; Rao, Vamkudoth Koteswara; Ramasamy, Sureshkumar (Protein and Peptide Letters, 2020)
One of the unique characteristic features of the domain archaea, are the lipids that form the hydrophobic core of their cell membrane. These membrane lipids are characterized by distinctive isoprenoid biochemistry and the building blocks are two core lipid structures, sn-2,3-diphytanyl glycerol diether (archaeol) and sn-2,3-dibiphytanyl diglycerol tetraether (caldarchaeol). Archaeol has two phytanyl chains (C-20 in a bilayer structure connected to the glycerol moiety by an ether bond. The enzyme involved in this bilayer formation is Di-O-Geranylgeranyl Glyceryl Phosphate Synthase (DGGGPS), which is a member of a very versatile superfamily of enzymes known as UbiA superfamily. Multiple sequence analysis of the typical members of the UbiA superfamily indicates that the majority of conserved residues are located around the central cavity of these enzymes. Interestingly few of these conserved residues in the human homologs are centrally implicated in several human diseases, on basis of the major mutations reported against these diseases in the earlier clinical studies. It remains to he investigated about the role of these conserved residues in the biochemistiy of these enzymes. The binding and active site of these enzymes found to be similar architecture but have different substrate affinities ranging from aromatic to linear compounds. So further investigation of UbiA superfamily may be translated to novel therapeutic and diagnostic application of these proteins in human disease management.
Keywords: Archeal lipids; biA superfamily; DGGGPS; genetic diseases; lipid synthesis; membrane protein

EGCG impedes human Tau aggregation and interacts with Tau - Sonawane, Shweta Kishor; Chidambaram, Hariharakrishnan; Boral, Debjyoti; Gorantla, Nalini Vijay; Balmik, Abhishek Ankur; Dangi, Abha; Ramasamy, Sureshkumar; Marelli, Udaya Kiran; Chinnathambi, Subashchandrabose (Scientific Reports, 2020)
Tau aggregation and accumulation is a key event in the pathogenesis of Alzheimer's disease. Inhibition of Tau aggregation is therefore a potential therapeutic strategy to ameliorate the disease. Phytochemicals are being highlighted as potential aggregation inhibitors. Epigallocatechin-3-gallate (EGCG) is an active phytochemical of green tea that has shown its potency against various diseases including aggregation inhibition of repeat Tau. The potency of EGCG in altering the PHF assembly of full-length human Tau has not been fully explored. By various biophysical and biochemical analyses like ThS fluorescence assay, MALDI-TOF analysis and Isothermal Titration Calorimetry, we demonstrate dual effect of EGCG on aggregation inhibition and disassembly of full-length Tau and their binding affinity. The IC50 for Tau aggregation by EGCG was found to be 64.2 mu M.